Rapid evolution of phenology during range expansion with recent climate change - Lustenhouwer, Nicky; Wilschut, Rutger A.; Williams, Jennifer L.; Putten, Wim H.; Levine, Jonathan M. (Global change biology, 2018)
Although climate warming is expected to make habitat beyond species’ current cold range edge suitable for future colonization, this new habitat may present an array of biotic or abiotic conditions not experienced within the current range. Species’ ability to shift their range with climate change may therefore depend on how populations evolve in response to such novel environmental conditions. However, due to the recent nature of thus far observed range expansions, the role of rapid adaptation during climate change migration is only beginning to be understood. Here, we evaluated evolution during the recent native range expansion of the annual plant Dittrichia graveolens, which is spreading northward in Europe from the Mediterranean region. We examined genetically based differentiation between core and edge populations in their phenology, a trait that is likely under selection with shorter growing seasons and greater seasonality at northern latitudes. In parallel common garden experiments at range edges in Switzerland and the Netherlands, we grew plants from Dutch, Swiss, and central and southern French populations. Population genetic analysis following RAD‐sequencing of these populations supported the hypothesized central France origins of the Swiss and Dutch range edge populations. We found that in both common gardens, northern plants flowered up to 4 weeks earlier than southern plants. This differentiation in phenology extended from the core of the range to the Netherlands, a region only reached from central France over approximately the last 50 years. Fitness decreased as plants flowered later, supporting the hypothesized benefits of earlier flowering at the range edge. Our results suggest that native range expanding populations can rapidly adapt to novel environmental conditions in the expanded range, potentially promoting their ability to spread. In order to persist under global climate change, many species must shift their range northward, but novel environmental conditions at higher latitudes may constrain range expansion. We found that the Mediterranean plant species Dittrichia graveolens evolved earlier flowering during its recent range expansion in Europe. At the northern range edge in the Netherlands, Dutch plants on average flowered 1 week earlier than plants from central France (their putative source region), and 4 weeks earlier than plants from southern France. Early‐flowering plants had a fitness advantage at the range edge, suggesting that rapid adaptation may promote range expansion with climate change.